2020
DOI: 10.1002/jcla.23602
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin as a key risk factor for nonalcoholic fatty liver disease in children with obesity

Abstract: Background The association between serum ferritin and nonalcoholic fatty liver disease (NAFLD) in children with obesity is not clear. This study was designed to investigate whether serum ferritin can be an independent predictor for NAFLD. Methods According to the hepatic ultrasound results, a total of 347 children with obesity were enrolled in this study. Among them, 95 patients with NAFLD and 95 without NAFLD were matched for gender, age, blood pressure and body mass index, the odds ratios (OR) and 95% confid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
1
12
1
Order By: Relevance
“…Previously, the correlation of serum ferritin and NAFLD has been incompletely studied in children. Ferritin levels in children with NAFLD were obviously higher than their counterparts in non‐NAFLD group 24 . A recent study by H.B.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Previously, the correlation of serum ferritin and NAFLD has been incompletely studied in children. Ferritin levels in children with NAFLD were obviously higher than their counterparts in non‐NAFLD group 24 . A recent study by H.B.…”
Section: Discussionmentioning
confidence: 80%
“…Ferritin levels in children with NAFLD were obviously higher than their counterparts in non‐NAFLD group. 24 A recent study by H.B. Kim et al 25 found serum ferritin level were positively associated with NAFLD in postmenopausal women.…”
Section: Discussionmentioning
confidence: 96%
“…Another cross-sectional study conducted in Guangzhou, China, found that among children with obesity attributed to BMI, ferritin levels in the dyslipidemia group were higher than those in the healthy fat group [ 35 ]. Other studies have also shown that ferritin is an independent risk factor for nonalcoholic fatty liver in children with obesity and in adolescents [ 36 , 37 ]. These findings suggested there is a synergistic effect of ferritin and obesity on abnormal lipid metabolism both in children and adults.…”
Section: Discussionmentioning
confidence: 99%
“…NAFLD was defined based on hepatic ultrasound, which was conducted to assess the presence and extent of hepatic steatosis according to the following guidelines: (a) a diffuse hyperechoic texture (bright liver); (b) increased liver echo texture compared to the kidney; (c) deep beam attenuation; (d) vascular blurring (absence of normal echogenic walls of the portal veins and hepatic veins). Exclusion criteria were: drugs and genetic metabolic liver disease, history of severe heart, liver, and kidney disease, type 1 diabetes mellitus, malignancy, pituitary disease, hyperprolactinemia, viral hepatitis; previous drinking history, and other related endocrine and metabolic diseases [12]. The study was approved by the Ethics Committee of Shaoxing Maternity and Child Health Care Hospital (No.…”
Section: Study Populationmentioning
confidence: 99%